INTEGRASI KEUNGGULAN LOKAL NTT DALAM PEMBELAJARAN BAHASA INDONESIA - dan Maria Rosalinda Talan, Imaniah Kusuma Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2020)
The government has long recomended lessons that include local advantages. One of the goals is that students can recognize, preserve, process and develop local advantages and also the purpose of contextualizing learning. However this recommendation is completely not followed by educators. The educators are more based on learning recources provided by the Ministry of Education and Culture so that they do not represent a real problem for students. Thus researcher helps educators to prepare lesson plans that integrate NTT’s local advantages. The aim is to observe the activities of student, student learning outcomes and the responses of educators and students to integration of NTT local excellence in Indonesian language learning. The research subjects were educators and students at SMP Negeri 1 Kefamenanu, SMP Negeri 2 Kefamenanu and SMP Negeri Neonbat. Data collection techniques that used in this research were observation, tests, and questionnaires. The results showed that the activity of students reached 78.33 % which was in the good category, the learning outcomes of students reached 79.21 % which was in the good category, the response of teachers and students the integration of local excellence in NTT reached 95.5 % which was included in the very good category. Nevertheless the integration of NTT’s local excellence in Indonesian language learning needs to be carried out continuously because it makes a positive contribution to the students. Key words: local advantages, Indonesian language learning.